1972
DOI: 10.2307/1540191
|View full text |Cite
|
Sign up to set email alerts
|

Axial Filament of Silicious Sponge Spicules, Its Organic Components and Synthesis

Abstract: 1. A substantial portion of the axial filament of the spicules of silicious sponges is protein. 2. The axial filament protein lacks the hydroxylated amino acids that are characteristically abundant in collagen. 3. It is feasible to follow the course of silicious deposition in spicules using C or H in protein precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Because the axial protein filament is occluded wholly within the silica spicule, it had long been suspected of participating in the control of biosilicification, although the mechanism by which it might do so remains unclear (24). Hecky et al (4) postulated that the hydroxyl-rich proteins of the silicified diatom wall might condense with silicic acid monomers, thus serving as scaffolds to organize the growth of the silica.…”
Section: Discussionmentioning
confidence: 99%
“…Because the axial protein filament is occluded wholly within the silica spicule, it had long been suspected of participating in the control of biosilicification, although the mechanism by which it might do so remains unclear (24). Hecky et al (4) postulated that the hydroxyl-rich proteins of the silicified diatom wall might condense with silicic acid monomers, thus serving as scaffolds to organize the growth of the silica.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cross section of the spicules in Fig. 4B shows a solid structure around the channel, whereas other sponges have a layered structure (Aizenberg et al, 2004;Levi et al, 1989;Shore, 1972;Uriz et al, 2000). To investigate the chemical nature of the junctions, spicules subjected to bleaching and heattreatment at 823 K are considered.…”
Section: Macroscopic Structure Of the Spongementioning
confidence: 99%
“…Siliceous spicules of demosponges are known to contain an axial filament composed of protein (Shore 1972). However, the mechanism of spicule formation had remained unclear until studies in two demosponges, Tethya aurantium Cha et al 2000;Shimizu et al 1998) and Suberites domuncula (Krasko et al 2000), revealed that the axial filament of siliceous spicule was enzymatically fabricated via a protein called silicatein.…”
Section: Spicule Formationmentioning
confidence: 99%
“…Spicule development and morphology have been characterised since the early 1900s (Bergquist and Sinclair 1973;Borojevic et al 1968;Schulze 1904;Shore 1972;Simpson 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation